Evaluasi Penerapan Akuntansi Syariah Berdasarkan PSAK No. 101 Dan No. 105 Pada Bank Syariah Indonesia Cabang Manado - Susanti Sa'ban; Michael Miran; Miryam Pinkan lonto (Fakultas Ekonomi Universitas Negeri Manado, 2022)
The purpose of this research was to evaluate the implementation of Islamic accounting based on PSAK no.101 and No.105 at Syariah Bank, Indonesia, Manado branch. The research method of this study is qualitative. The result indicated the implementation of Islamic accounting based on PSAK No. 101 and No. 105 at Syariah Bank, particularly in the financial statements, show the position of financial, income statement and other comprehensive income by the bank had been adjusted to the financial accounting standards in PSAK No. 101 and 105. This is evidenced based on the financial statement data that has been presented by the company and interview sources from several sources regarding Mudharabah Accounting.